2018
DOI: 10.2147/ndt.s180569
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural networks and connectomes: the brain–obesity interface and its impact on mental health

Abstract: PurposeObesity is a complex and multifactorial disease identified as a global epidemic. Convergent evidence indicates that obesity differentially influences patients with neuropsychiatric disorders providing a basis for hypothesizing that obesity alters brain structure and function associated with the brain’s propensity toward disturbances in mood and cognition. Herein, we characterize alterations in brain structures and networks among obese subjects (ie, body mass index [BMI] ≥30 kg/m2) when compared with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
(49 reference statements)
2
20
1
Order By: Relevance
“…In sum, participants with high depressive symptoms engaged more in a state characterized by an increased coupling of the precuneus with regions in the DM network (PL state 3), and less in a state where the precuneus shifts away from connections in this network (PL state 8). We proposed that this imbalance might result in maladaptive cognitive styles that ultimately contribute to sad mood and depressive symptoms, which aligns with other studies implicating abnormal FC of the precuneus in patients with depression (Sheline et al, 2009;Li et al, 2013;Chen et al, 2018).…”
Section: Dynamical Properties Of Fc Disentangle the Distinct Role Of supporting
confidence: 87%
“…In sum, participants with high depressive symptoms engaged more in a state characterized by an increased coupling of the precuneus with regions in the DM network (PL state 3), and less in a state where the precuneus shifts away from connections in this network (PL state 8). We proposed that this imbalance might result in maladaptive cognitive styles that ultimately contribute to sad mood and depressive symptoms, which aligns with other studies implicating abnormal FC of the precuneus in patients with depression (Sheline et al, 2009;Li et al, 2013;Chen et al, 2018).…”
Section: Dynamical Properties Of Fc Disentangle the Distinct Role Of supporting
confidence: 87%
“…Twenty-one out of twenty-eight retrieved studies [23][24][25][26][27][28]32,33,46,[49][50][51][52][53][54][55][56][57][58][59] used samples of adults. Five studies [60][61][62][63][64] were performed on adolescents between 12 and 19 years, and two studies 65,66 were performed on children between 7 and 11 years.…”
Section: Sample Types and Dti Approachmentioning
confidence: 99%
“…Five studies [60][61][62][63][64] were performed on adolescents between 12 and 19 years, and two studies 65,66 were performed on children between 7 and 11 years. Twenty-six studies [23][24][25][26][27][28]32,33,46,50,[52][53][54][56][57][58][60][61][62][63][64][65][66][67][68][69] used a sample composed of both men and women, while two studies 59,70 were performed on women only. All selected studies used a crosssectional approach.…”
Section: Sample Types and Dti Approachmentioning
confidence: 99%
“…While some have postulated that shared genetic risks 33 and the underlying chronic inflammatory state in obesity are a common link in noted psychiatric alterations, 34 others report that structural changes in the brain in severe obesity may be a potential contributor to mood and emotional changes. 35 Diffusion indices which measure structural connectivity in areas of the brain that control feeding behaviours have been shown to correlate negatively with BMI, depression and anxiety symptoms. 35 Whether changes in the hormonal milieu observed in states of severe obesity cause these structural changes is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…35 Diffusion indices which measure structural connectivity in areas of the brain that control feeding behaviours have been shown to correlate negatively with BMI, depression and anxiety symptoms. 35 Whether changes in the hormonal milieu observed in states of severe obesity cause these structural changes is yet to be determined. 23 Another study in 37 adolescents who underwent RYGB showed fewer symptoms of anxiety and depression 4 months after surgery.…”
Section: Discussionmentioning
confidence: 99%